Role of Weakly Adsorbed Water in the Photocatalytic Decomposition of Formic Acid on Pt/TiO2 - Woo Lee, Chul (Asian Journal of Chemistry, 2013)
Photocatalysis is an effective method of oxidizing or decomposing organic contaminants present in low concentrations in the air at room temperature. The rate of photocatalytic decomposition of formic acid on 0.2 % Pt/TiO2 was studied using transient isothermal reaction and temperature programmed desorption. Formic acid is of interest because it is an intermediate oxidation product of many organics. Transient photocatalytic decomposition shows that water co-adsorbed with formic acid does not significantly affect the rate of decomposition. Water is weakly adsorbed, however, significantly increases the rate. Only hydrogen was formed and any other product such as oxygen or carbon dioxide was not produce when water was injected in the reactor in the dark after photocatalytic decomposition of formic acid. It is inferred that the role of weakly adsorbed water is to replenish the vacant lattice oxygen of TiO2 surface which are the main reason for the rate decrease.